2016
DOI: 10.1007/s10934-016-0147-6
|View full text |Cite
|
Sign up to set email alerts
|

Diatom frustules as a biomaterial: effects of chemical treatment on organic material removal and mechanical properties in cleaned frustules from two Coscinodiscus species

Abstract: The three-dimensional structure of silica diatom frustules offers a great potential as nanoporous material for several nanotechnological applications, but the starting point for these applications is the ability to obtain clean frustules with sufficient mechanical strength and intact structure. Here, frustules from the diatoms Coscinodiscus centralis Ehrenberg and C. wailesii Gran et Angst are characterized with respect to their structural integrity, content of residual organic biomaterial and their mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…While we have not found studies that specifically test the method used here, it is a very potent oxidation method 31 and Romann et al . 32 tested a similar harsh method (hydrogen peroxide) and compared it to a milder method (a combination of a surfactant and a complexing agent) and found that there was no fluorescence signal from organic material after treatment by the harsh method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we have not found studies that specifically test the method used here, it is a very potent oxidation method 31 and Romann et al . 32 tested a similar harsh method (hydrogen peroxide) and compared it to a milder method (a combination of a surfactant and a complexing agent) and found that there was no fluorescence signal from organic material after treatment by the harsh method.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that organic components imbedded in the frustules are not completely removed by the oxidation and that these may influence the spectral properties of rinsed frustules of the three species deserves to be explored for two reasons: Although we expect that the relatively harsh oxidation employed in the present study has probably removed most organic material, other methods used for cleaning diatom valves have been shown to leave remains of organic material in the silica matrix 29 , 32 and this possibility is therefore relevant for industrial applications using a range of oxidation methods. The organic templates are species-specific 30 , and might therefore contribute to the differences in UV filtering effect.…”
Section: Discussionmentioning
confidence: 99%
“…Diatom frustules retain impurities (such as inorganic oxides Al 2 O 3 , Fe 2 O 3 , CaCO 3 , CaO) mainly due the local environment and aging conditions [34]. The treatment of frustules with acid solutions (e.g., sulfuric acid-, hydrochloric acid-based solutions) at different strengths is a valid purification strategy to remove impurities, making them suitable and safe for biomedical applications [35,36]. However, it is fundamental to balance properly the acid solution strength, in order to keep frustule structure integrity.…”
Section: Diatoms: a Natural Source Of Nanostructured Biosilicamentioning
confidence: 99%
“…Thus, diatoms biosilica could be obtained after proper purification treatments (e.g. sulfuric acid-, hydrochloric acid-based solutions) in order to remove impurities, making diatom frustules suitable and safe for biomedical applications [35][36][37]. The diatoms biosilica structure after acid/oxidative cleaning can be easily manipulated as micro or nano multifunctional scaffold by various chemical modifications, opening the way to new class of bioengineered nanostructured materials for biomedical applications [18,38,39].…”
Section: Diatoms: a Natural Source Of Nanostructured Biosilicamentioning
confidence: 99%